PENGARUH PEMBERIAN KULIT PISANG KEPOK TERFERMENTASI TERHADAP TOTAL PROTEIN PLASMA DAN GLUKOSA DARAH PADA DOMBA EKOR TIPIS - Rinjani, Nadinda Khoirunnisa Puri; Adhianto, Kusuma; Liman, Liman; Siswanto, Siswanto (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2025)
This research aims to determine the best treatment for male thin-tailed sheep by examining the effect of fermented banana peel supplementation on blood glucose levels and total plasma protein. This research used a Randomized Block Design (RBD) with 15 male thin-tailed sheep divided into 5 groups. There were 3 treatments with 5 replications, namely: P0 (50% concentrate and 50% corn cob silage), P1 (50% concentrate, 35% corn cob silage, 15% fermented banana peel silage), and P2 (50% concentrate, 20% corn cob silage, 30% fermented banana peel silage). The variables measured included plasma protein and blood glucose levels. Data were analyzed using Analysis of Variance, with the Least Significant Difference (LSD) test at a significance level of 5% and 1% for variables that had a significant effect. The administration of fermented banana peel did not significantly affect the total plasma protein levels (P0: 6.08±0.40; P1: 6.12±0.54; P2: 6.28±0.33 g/dl) or blood glucose levels (P0: 48.6±5.32 mg/dl; P1: 43.2±16.15 mg/dl; P2: 49.6±4.04 mg/dl). This treatment did not affect blood glucose levels or total plasma protein in thin-tailed sheep